Adhesion between steel slag aggregates and bituminous binder based on surface characteristics and mixture moisture resistance. (20th December 2020) - Moura, Bárbara Luiza Riz de; Teixeira, Jamilla Emi Sudo Lutif; Simão, Renata Antoun; Khedmati, Mahdieh; Kim, Yong-Rak; Pires, Patrício José Moreira
Highlights: Binder-slag adhesion assessment based on small scale characterization. Air-cooled blast furnace (ACBFS) slag and Linz-Donawitz (LD) slag were examined. Chemical and surface energy characteristics affects binder-slag adhesion. The AFM appeared as a promising method to evaluate binder-aggregate adhesion. Small-scale surface characteristics agreed well with the large-scale observations. Abstract: Steel slag aggregates (SSA) have shown promising mechanical and physical properties for asphalt concrete application. However, SSA surface characteristics vary depending on the type of slag, which results in different binder-SSA adhesion that affects moisture damage of asphalt mixtures containing SSA. This study evaluated the adhesion in the binder-SSA system considering two typical types of slags (i.e. air-cooled blast furnace slag (ACBFS) and Linz-Donawitz steel slag (LD)) using various tests: morphological, physical, chemical, and surface energy measurements. Also, the moisture damage susceptibility of asphalt mixtures containing SSA were assessed based on two standard methods: ASTM D3625 and AASHTO T283. Test results showed strong influence of the SSA chemical composition and surface energy characteristics on the SSA-binder adhesion. LD showed a better adhesion with the asphalt binder than ACBFS due to its particular chemical and surface energy characteristics. The diminished adhesive bonding from ACBFS could be improved with proper surface treatment using additives such as hydrated lime and electrostatic precipitator powder, which change surface chemistry of ACBFS.